Model Pemanfaatan Sumberdaya Perikanan Tangkap dengan Aspek Sustainability - Suharno Suharno; Irma Suryahani (EKO-REGIONAL, 2010)
The aim of study is to estimate the catch and effort at the level of maximum sustainable catches (MSY), Maximum Economic Yield (MEY), and Open Access (OA). MSY, MEY, and bioekonomi OA are an indicator that will be used to formulate a fisheries management in Cilacap regency. Bioekonomi analysis results used to formulate appropriate policies in the management of shrimp resources in the district of Cilacap. This study specifically uses trammel nets as an approach to the analysis of the shrimp resource stocks. Analysis tool used is the model bioekonomi Fox (Anderson, 1986). Fox model is more suitable for estimating the stock of shrimp in Cilacap regency. Further analysis in this study using the model of Fox. The results showed that the catch and effort at the level of Maximum Sustainable Yield (MSY) of 1806 tons/year and 10,104 trip/year. The estimated value of Maximum Economic Yield (MEY) and Open Access (OA) at the level of 1736 tons/year; 7518 trip/year; and 1258 tons/year; 21,288 trip/year. The level of benefits (economic rent) at MSY is Rp39,296,177,312, MEY is Rp41,978,949,609 and EOA of Rp0,-.  Trammel nets Net Profitability for Rp174.391/trip. Fox model analysis showed that it occurred more catches (overfishing) since 1986-2008 with the level of the average utilization of 121.42%. Some forms of fisheries management proposed in this study among others: restrictions on shrimp fishing quotas at the level of MSY of 179 Kg/Trip and to MEY 230 Kg/Trip; policy on optometry wide net; conservation efforts; control of the seasons/fishing area (spawning ground and fishing ground); rotation in the conduct of fishing (fishing with alternate day); limiting the issuance of new arrests for the ship; Co-management among stakeholders; Law Enforcement (enforcement) and control (Surveillance) and Fisheries Information System (FIS ) capture fisheries as the basis for policy resource utilization and management of shrimp.  Keywords:shrimp, bioekonomi, model fox, overfishing